Development of relative body mass (BMI) of students from Łódź, depending on the selected environmental, psychological and sociological factors - Pruszkowska-Przybylska, Paulina; Skowyra, Katarzyna; Sękowski, Piotr (Anthropological Review, 2016)
The human height-to-weight ratio is an important parameter of the body homeostasis. Currently, the most popular measurement determining the relationship between body mass and height is the Quetelet II indicator, called Body Mass Index (BMI). The aim of this study is an evaluation of the differences in the height-to-weight ratios, depending on selected environmental, psychological and sociological factors in people studying at higher education institutions in Łódź. The research was conducted among students of higher education institutions in Łódź, by electronic means or with the use of an anonymous survey. It consisted of 28 closed single or multiple choice questions. Statistical analysis was made of complete results of the research involving 135 people, both males and females, aged between 19-26. It was revealed that the factors related to higher BMI values in students are the following: the presence of a tendency in the students to gain weight themselves, and a tendency to gain weight present in their mothers, an evaluation of their own body mass as excessive, regularly smoking cigarettes and rarely undergoing medical check-ups. Among the factors connected with lower BMI values are: regular coffee consumption, perception of their own body mass as being too low, and also obtaining systolic pressure values below 110 mm Hg. Additionally, a positive correlation between taking up physical activity and higher values of systolic blood pressure (p<0.05) was shown. Among the subjects, it was found that 92% of the underweight women declared that their body mass and figure were normal. In the case of women with optimal BMI values, 40% stated that their body mass was excessive. In the case of men the problem was reverse: 50% of the subjects who were either overweight or obese claimed that their body mass was within the norm. The factors that significantly influence body proportion differences among students include the subject’s and the subject’s mother’s tendency to put on weight, self-evaluation of their own body mass, the values of systolic blood pressure, coffee consumption and cigarette smoking, as well as the frequency of medical check-ups.